MENINGKATKAN LITERASI WIRAUSAHA MELALUI PELATIHAN STRATEGI MARKETING PADA UKM GOYANG 1.1 KABUPATEN KUBU RAYA - Syamsuri Syamsuri; Nuraeni Asriati; Junaidi H. Matsum; Achmadi Achmadi; Witarsa Witarsa; Muhammad Basri; Husni Syahrudin (Jurnal Abdimas Bina Bangsa, 2023)
The development of the current digital era has touched all lines of life, including in the business world such as marketing. Marketing is an absolute thing that must be done in the business world. The problem that is often encountered is that not all people, such as SMEs, understand modern marketing or digital marketing, so the marketing model is still conventional. Finally, the information conveyed is limited. Digital-based marketing is marketing that utilizes the internet, so that the reach is wider, but still minimal expenses. One of the business units facing this is the rengginang Goyang 1.1 UKM. Based on this, education related to digital marketing or online-based marketing needs to be done in this place. One way that can be taken is by doing community service, which is carried out by a team of college lecturers. The purpose of this activity is to provide education to partners regarding online-based marketing methods. The hope of the service team this time is that the UKM actors who have been educated will be able to educate the UKM actors who have not had the chance to take part in this activity. The method used for realization is through lectures. The results of the dedication show that PKM activities can increase the participants' knowledge from 39% to 61%, all participants' responses are also positive. This means that the PKM activity has been successful according to the activity target